Predictors of Incisional Hernia after Robotic Assisted Radical Prostatectomy. (2nd February 2015) - Chennamsetty, Avinash; Hafron, Jason; Edwards, Luke; Pew, Scott; Poushanchi, Behdod; Hollander, Jay; Killinger, Kim A.; Coffey, Mary P.; Peters, Kenneth M.
Abstract : Introduction. To explore the long term incidence and predictors of incisional hernia in patients that had RARP. Methods. All patients who underwent RARP between 2003 and 2012 were mailed a survey reviewing hernia type, location, and repair. Results. Of 577 patients, 48 (8.3%) had a hernia at an incisional site (35 men had umbilical), diagnosed at (median) 1.2 years after RARP (mean follow-up of 5.05 years). No statistically significant differences were found in preoperative diabetes, smoking, pathological stage, age, intraoperative/postoperative complications, operative time, blood loss, BMI, and drain type between patients with and without incisional hernias. Incisional hernia patients had larger median prostate weight (45 versus 38 grams;P = 0.001 ) and a higher proportion had prior laparoscopic cholecystectomy (12.5% (6/48) versus 4.6% (22/480);P = 0.033 ). Overall, 4% (23/577) of patients underwent surgical repair of 24 incisional hernias, 22 umbilical and 2 other port site hernias. Conclusion. Incisional hernia is a known complication of RARP and may be associated with a larger prostate weight and history of prior laparoscopic cholecystectomy. There is concern about the underreporting of incisional hernia after RARP, as it is a complication often requiring surgical revision and is of significance for patient counseling before surgery.